﻿Recent advances in the pharmacotherapy of osteoarthritis - Muthu Meera (Research Results in Pharmacology, 2022)
Introduction: Osteoarthritis (OA) is a common debilitating disease affecting the geriatric population. Management of osteoarthritis is a challenge for orthopedicians because till date there has been no such drug that can completely cure the disease or at least retard/arrest the disease progression. In addition to the currently available treatment options for OA like NSAIDs, opioids, nutraceuticals (glucosamine sulphate and chondroitin sulphate), many new drugs are being discovered or repurposed for use in osteoarthritis. Most of these recent drugs aim at retarding the disease progression rather than providing just a symptomatic relief. Materials and methods: All relevant articles regarding approved new drugs and pipeline drugs for osteoarthritis published between 2012–2021 were analysed. Those included animal studies as well as clinical trials. Some older articles were also referred to, provided they highlighted any significant data. The obtained data were analysed and compiled. Results and discussion: Broadly the recent drugs for OA can be classified based upon their site of action as (i) drugs targeting articular cartilage, (ii) drugs targeting inflammation, (iii) drugs targeting the subchondral bone, and (iv) drugs for relieving pain. Ranging from in vitro studies to clinical trials, these drugs are in various phases of drug discovery. Early diagnosis of OA and its management with a drug that retards disease progression rather than prescribing just a symptom reliever is very much necessary in the current situation. Conclusion: Need for new drugs for OA is increasing day by day. More number of clinical trials with larger sample sizes alone can satisfy the need of disease modifying drugs for OA. This review provides a deep insight into all the recent advances in the pharmacotherapy of osteoarthritis. Graphical abstract: